2004
DOI: 10.1038/sj.onc.1207987
|View full text |Cite
|
Sign up to set email alerts
|

Differential immunization identifies PHB1/PHB2 as blood-borne tumor antigens

Abstract: Early diagnosis of cancer is crucial for successful treatment. Noninvasive assays for detecting tumor-derived antigens in serum and other bodily fluids have the potential to screen healthy individuals for hitherto undetected cancers. Very few such assays have been successfully developed, in part because identifying potential target antigens remains a challenge. To identify new blood-borne tumor antigens for the purpose of establishing such assays, we have developed a novel technique called differential immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…The increased expression of cell-surface PHB1 on drug-resistant cells further suggests that cell-surface PHB1 on cells in solid tumors or particularly on circulating tumor cells could provide a marker for the detection of taxane resistance in cancer patients either before or during the course of chemotherapy. PHB1 can also circulate independently and has been shown to be increased in the serum of patients with colorectal cancer (42). The relevance of this increased level of circulating PHB1 to any form of drugresistance has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of cell-surface PHB1 on drug-resistant cells further suggests that cell-surface PHB1 on cells in solid tumors or particularly on circulating tumor cells could provide a marker for the detection of taxane resistance in cancer patients either before or during the course of chemotherapy. PHB1 can also circulate independently and has been shown to be increased in the serum of patients with colorectal cancer (42). The relevance of this increased level of circulating PHB1 to any form of drugresistance has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…PHB1 (51,53), PHB2 (56), and PHB1⅐PHB2 complexes (14,57) associate with plasma membrane lipid rafts that are believed to modulate many intracellular signaling events. Overexpression of PHB1 in 3T3-L1 fibroblasts up-regulates basal ERK MAPK signaling, leading to adipogenesis (58).…”
Section: Discussionmentioning
confidence: 99%
“…For example, decreased expression of PHB was reported in human stomach adenocarcinoma tissue compared with the surrounding normal tissues [5]. However, a number of studies report high-level expression of PHB in other tumor tissues, such as lung cancer, prostate carcinoma [6], and rat bladder carcinomas [7]. Studies have also shown that PHB levels are higher in transformed cells and tumors than in their normal counterparts [7][8][9].…”
mentioning
confidence: 93%